The career goals of nurses in some health care settings in Gauteng - Jooste, K (Curationis (Pretoria), 2005)
In nursing, purposeful career planning is essential if nurse practitioners want to make the right decisions about their work in order to strive towards and accomplish a meaningful quality of working life. Nurses should identify their career goals to be able to investigate their different career opportunities in their field of interest and direct their work according to a work strategy for years ahead. The purpose of this study was to explore and describe the career goals of post-basic nursing students with the aim of describing management strategies to guide the future career of post-basic nursing students in climbing the career ladder effectively and obtaining their set career goals. An explorative, descriptive, qualitative design was selected where the researcher worked inductively to explore and describe the needs (goals) and future planned actions of the participants regarding their career management as viewed for a period of five years. The researcher purposively and conveniently identified the sample as all the post-basic nursing students, namely 250 students, who were registered for the first, second and third year of nursing management courses in that period at a South African residential university. Two structured, open questions were developed. Each participant received the questions in writing and was asked to answer them. The QSR NUD*IST program was used for the qualitative management (categorization) of data. The results of the research questions related to five categories, namely becoming empowered, being promoted, being educated and professionally developed, partaking in research and taking up new projects.